Inflammatory cytokines associated with cancer growth induce mitochondria and cytoskeleton alterations in cardiomyocytes. Issue 11 (14th April 2019) - Buoncervello, Maria; Maccari, Sonia; Ascione, Barbara; Gambardella, Lucrezia; Marconi, Matteo; Spada, Massimo; Macchia, Daniele; Stati, Tonino; Patrizio, Mario; Malorni, Walter; Matarrese, Paola; Marano, Giuseppe; et al.
Abstract: Cardiac dysfunction is often observed in patients with cancer also representing a serious problem limiting chemotherapeutic intervention and even patient survival. In view of the recently established role of the immune system in the control of cancer growth, the present work has been undertaken to investigate the effects of a panel of the most important inflammatory cytokines on the integrity and function of mitochondria, as well as of the cytoskeleton, two key elements in the functioning of cardiomyocytes. Either mitochondria features or actomyosin cytoskeleton organization of in vitro‐cultured cardiomyocytes treated with different inflammatory cytokines were analyzed. In addition, to investigate the interplay between tumor growth and cardiac function in an in vivo system, immunocompetent female mice were inoculated with cancer cells and treated with the chemotherapeutic drug doxorubicin at a dosing schedule able to suppress tumor growth without inducing cardiac alterations. Analyses carried out in cardiomyocytes treated with the inflammatory cytokines, such as tumor necrosis factor α (TNF‐α), interferon γ (IFN‐γ), interleukin 6 (IL‐6), IL‐8, and IL‐1β revealed severe phenotypic changes, for example, of contractile cytoskeletal elements, mitochondrial membrane potential, mitochondrial reactive oxygen species production and mitochondria network organization. Accordingly, in immunocompetent mice, the tumor growth was accompanied by increased levels of the inflammatory cytokines TNF‐α, IFN‐γ, IL‐6, and IL‐8, either in serum or in the heart tissue, together with a significant reduction of ventricular systolic function. The alterations of mitochondria and of microfilament system of cardiomyocytes, due to the systemic inflammation associated with cancer growth, could be responsible for remote cardiac injury and impairment of systolic function observed in vivo. Abstract : Cardiac dysfunction is often observed in patients with cancer. The alterations of mitochondria and of microfilament system of cardiomyocytes, due to the systemic inflammation associated with cancer growth could be responsible for remote cardiac injury and impairment of systolic function observed in vivo.